Examination of the evolution of iron oxide nanoparticles in flame spray pyrolysis by tailored in situ particle sampling techniques. (May 2021) - Tischendorf, R.; Simmler, M.; Weinberger, C.; Bieber, M.; Reddemann, M.; Fröde, F.; Lindner, J.; Pitsch, H.; Kneer, R.; Tiemann, M.; Nirschl, H.; Schmid, H.-J.
Abstract: In this report, a flame spray pyrolysis setup has been examined with various in situ extraction methods of particle samples along the flame axis. First, two precursor formulations leading to the formation of iron oxide nanoparticles were used in a standardized SpraySyn burner system, and the final particle outcome was characterized by a broad range of established powder characterization techniques (TEM/HRTEM, SAXS, XRD, BET). The characterization of the powder products evidenced that mostly homogeneous gas-to-particle conversion takes place when applying an acidic precursor solution, whereas the absence of the acid leads to a dominant droplet-to-particle pathway. Our study indicates that a droplet-to-particle-pathway could be present even when processing the acidic formulation. However, even if a secondary pathway might take place in this case as well, it is not dominant and nearly negligible. Subsequently, the in situ particle structure evolution was investigated for the dominant gas-to-particle pathway, and particles were extracted along the flame axis for online SMPS and offline TEM/HRTEM analysis. Due to the highly reactive conditions within the flame (high temperatures, turbulent flow field, high particle number concentrations), the extraction of representative samples from spray flames is challenging. In order to handle the reactive conditions, two extraction techniques were tailored in this report. To extract an aerosol sample within the flame for SMPS measurement, a Hole in a Tube probe was adjusted. Thus, the mobility particle diameter as well as the corresponding distribution widths were obtained at different heights above the burner along the flame axis. For TEM/HRTEM image analysis, particle samples were collected thermophoretically by means of a tailored shutter system. Since all sampling grids were protected until reaching the flame axis and due to the low sampling time, momentary captures of local particle structures could be extracted precisely. The particle morphologies have clearly shown an evolution from spherical and paired particles in the flame center to fractal and compact agglomerates at later synthesis stages. Highlights: In situ sampling via Hole-in-a-Tube probes from Flame Sprays. Sampling via shutter systems with precise local shorttime sampling for HRTEM analysis. Flame spray pyrolysis gas-to-particle route results in a variety of extremely small particle structures. Observation of droplet-to particle routes for iron nitrate based precursor formulations. Insights into the particle structure evolution along the flame axis reveal locally dominating formation mechanisms.